Project proposal for Mellon Supra-institutional project on the Decolonial turn (unsettling paradigms) – 2018 - Bock, Zannie; Stroud, Christopher (Multilingual Margins: A journal of multilingualism from the periphery, 2023)
This is a proposal text submitted to the Mellon Foundation entitled "Languages and Literacies in Higher Education: Reclaiming voices from the south", to secure funding for the module.